2016
DOI: 10.1007/s10461-016-1578-4
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Attacks on the Dignity of Members of HIV Key Populations: A Descriptive and Exploratory Study

Abstract: Attacks on peoples’ dignity help to produce and maintain stigmatization and interpersonal hostility. As part of an effort to develop innovative measures of possible pathways between structural interventions or socially-disruptive Big Events and HIV outbreaks, we developed items to measure dignity denial. These measures were administered to 300 people who inject drugs (PWID), 260 high-risk heterosexuals who do not inject drugs (HRH), and 191 men who have sex with men who do not inject drugs (MSM). All of the PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Positive healthcare engagement in SSP settings established feelings of value and self-worth for PWID, which could have played a role in mitigating internalized drug use stigma following negative experiences at hospitals and local clinics [27]. Dignity may play a role in explaining this phenomenon as previous work has found that denying the dignity of vulnerable populations (i.e., PWID) may predispose them to increased stress and risky behaviors, which may in turn lead to poor health outcomes [29]. Our finding of the critical importance of SSPs in the delivery of effective, non-stigmatizing medical care has important public health policy implications and should be investigated further as a mode of healthcare delivery for vulnerable populations like PWID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive healthcare engagement in SSP settings established feelings of value and self-worth for PWID, which could have played a role in mitigating internalized drug use stigma following negative experiences at hospitals and local clinics [27]. Dignity may play a role in explaining this phenomenon as previous work has found that denying the dignity of vulnerable populations (i.e., PWID) may predispose them to increased stress and risky behaviors, which may in turn lead to poor health outcomes [29]. Our finding of the critical importance of SSPs in the delivery of effective, non-stigmatizing medical care has important public health policy implications and should be investigated further as a mode of healthcare delivery for vulnerable populations like PWID.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the impact of dignity should also be considered in the attempt to lessen drug use stigma and improve care for PWID. As adapted to substance use among PWID from an HIV paradigm, many stigmatized individuals' dignity is attacked as a result of the drug use label [29]. As such, political campaigns and social movements aiming to disband attacks on PWIDs' dignity, and to recognize and understand substance use disorders as medical entities may improve narratives of internalized drug use stigma among PWID, improve access to non-stigmatizing care, and ultimately may lead to improvements in health for PWID [1,29,31].…”
Section: Discussionmentioning
confidence: 99%
“…The enacted stigma that people who use drugs face from society, as well as the associated adverse effects on risk behavior and health outcomes, is well-documented. For example, research by Friedman et al ( 2017 ) showed that after people who inject drugs experienced interpersonal attacks on their dignity, they partook in riskier health behaviors, such as needle sharing. Similarly, an Australian study found that among people who inject drugs, those who reported discrimination in the past 12 months had elevated rates of overdose, diminished physical functioning, and mental illness (Couto e Cruz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, drug use stigma has been associated with discrimination (Ahern, Stuber & Galea, 2007;Earnshaw, Smith & Copenhaver, 2013) and may lead to greater social isolation (Akdağ et al, 2018;Rapier, McKernan & Stauffer, 2019). Furthermore, PWID tend to experience greater discrimination, and negative health consequences resulting from discrimination, because injection drug use is more stigmatizing than non-injection drug use (Friedman et al, 2017). Given these studies, it may be possible that drug use stigma impedes the development of social networks, however, it could also create bonds of solidarity.…”
Section: Gay and Bisexual Identitymentioning
confidence: 99%